The Impact of Digitalization on Maritime Operations: Exploring Emerging Technologies in Management and Education - Winarno Winarno; Larsen Barasa; Damoyanto Purba; Susi Herawati; Firdaus Bintang Cahyanti; Hazbi Aziz Ashshiddiqi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores the transformative impact of digitalization on maritime operations, focusing on emerging technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and blockchain. Through qualitative research and descriptive analysis, perspectives from maritime professionals, lecturers, and graduates were examined to understand the integration of these technologies in maritime management, operations, and education. The findings reveal that digital tools significantly enhance operational efficiency, decision-making, and sustainability while highlighting challenges in workforce training and the gap between theoretical knowledge and practical application in maritime education. Despite the benefits, full optimization of these technologies is still developing due to varied adoption levels across the industry. The research emphasizes the need for investment in infrastructure, continuous professional development, and educational reform to fully leverage digitalization in the maritime sector.